Effect of Coptis chinensis on Biofilm Formation and Antibiotic Susceptibility in Mycobacterium abscessus. (10th November 2020) - Tseng, Cheng-Yin; Sun, Mao-Feng; Li, Tsai-Chung; Lin, Ching-Ting
Abstract : Mycobacterium abscessus infections are notoriously difficult to be treated and newer treatment options are required. Coptis chinensis ( C. chinensis ) and its main compound berberine are frequently used to treat bacterial and viral infections. In this study, the susceptibility of M. abscessus to C. chinensis extract and berberine was assessed by minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) evaluation. The effects of C. chinensis and berberine on biofilm formation and antibiotic susceptibility in M. abscessus were observed. C. chinensis at concentrations of MIC (1.5 mg/mL) and 2 × MIC (3.0 mg/mL) and berberine at ½ × MIC (0.125 mg/mL) demonstrated a strong inhibition of biofilm formation. Concentration of C. chinensis at ½ × MIC resulted in a significant reduction in MICs of trimethoprim/sulfamethoxazole (TMP/SXT), clarithromycin (CLA), and linezolid (LZD). Similarly, ½ × MIC berberine had a significant effect on the MIC reductions of nine antibiotics including TMP/SXT, CLA, and LZD. Notably, the resistance level MIC of LZD against M. abscessus was reversed to a susceptible level by treatment with either C. chinensis or berberine. Therefore, C. chinensis and berberine have the potential to produce a synergistic antimycobacterial effect, reduce biofilm formation, and decrease antibacterial resistance to LZD in M. abscessus .